2020
DOI: 10.3390/ijms21103679
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Bone Aging

Abstract: A decline in bone mass leading to an increased fracture risk is a common feature of age-related bone changes. The mechanisms underlying bone senescence are very complex and implicate systemic and local factors and are the result of the combination of several changes occurring at the cellular, tissue and structural levels; they include alterations of bone cell differentiation and activity, oxidative stress, genetic damage and the altered responses of bone cells to various biological signals and to mechanical lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 98 publications
0
56
0
6
Order By: Relevance
“…Both runt-related transcription factor 2 (Runx2) [ 10 ] and Osterix (Osx) [ 11 ], also known as SP7 in human [ 12 ], control osteoblastic differentiation of MSCs [ 9 ]. Osteogenic differentiation can be enhanced by bone morphogenetic proteins (BMPs), a member of the transforming tumor growth factor (TGF) superfamily, through increasing Runx2 expression, which in turn raises Osx/SP7 expression [ 13 ]. Conversely, Wnt signaling inhibits adipogenesis by stimulating Runx2 and inhibiting CCAAT-enhancer binding protein α (C/EBP α) [ 13 ].…”
Section: Osteoporosismentioning
confidence: 99%
See 2 more Smart Citations
“…Both runt-related transcription factor 2 (Runx2) [ 10 ] and Osterix (Osx) [ 11 ], also known as SP7 in human [ 12 ], control osteoblastic differentiation of MSCs [ 9 ]. Osteogenic differentiation can be enhanced by bone morphogenetic proteins (BMPs), a member of the transforming tumor growth factor (TGF) superfamily, through increasing Runx2 expression, which in turn raises Osx/SP7 expression [ 13 ]. Conversely, Wnt signaling inhibits adipogenesis by stimulating Runx2 and inhibiting CCAAT-enhancer binding protein α (C/EBP α) [ 13 ].…”
Section: Osteoporosismentioning
confidence: 99%
“…Osteogenic differentiation can be enhanced by bone morphogenetic proteins (BMPs), a member of the transforming tumor growth factor (TGF) superfamily, through increasing Runx2 expression, which in turn raises Osx/SP7 expression [ 13 ]. Conversely, Wnt signaling inhibits adipogenesis by stimulating Runx2 and inhibiting CCAAT-enhancer binding protein α (C/EBP α) [ 13 ]. Excessive oxidative stress may cause increased reactive oxygen species (ROS), increased phosphorylation of p53 and p66, and decreased expression of β-catenin, leading to apoptosis of osteoblasts [ 14 , 15 , 16 , 17 ].…”
Section: Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that vitamin D supplementation in PCOS women may improve the steroidogenesis and enzymatic antioxidant activity in the human GC [ 94 ] and it may attenuate the actions of AGEs [ 95 , 96 ]. AGEs play a role in age-related bone loss [ 97 , 98 ]. AGEs provoke bone cell impairment and alter bone biomechanical properties.…”
Section: Vitamin D and Pcosmentioning
confidence: 99%
“…Moreover, osteoblast and osteoclast recruitment and activity can be affected by different cytokines. The inflammatory cytokines, for example, tumor necrosis factor α and the interleukins 1, 6 and 17, promote the generation of osteoclasts and their activity, while at the same time inhibit osteoblast differentiation and function [47]. These processes may also contribute to the loss of muscle mass and the development of sarcopenia [2,3].…”
Section: Diet and Bone Healthmentioning
confidence: 99%